Integral Notion of Love – The Foundation of Spirituality - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 1997)
The article analyses the holistic, integral approach to love, which helps to reveal the essence of love, to see the criteria of mature love, to highlight the principles and conditions of love. According to the insights of E. Fromm, P. Maldeikis, K. Wojtyla, A. Paškus and others, it is claimed that love is a specific and complex form of relationship with the world, which unfolds through contacts with different objects and phenomena: man, nature, culture, God. Love, as the ideal form of relations, gives rise to direction, meaning and fulfilment of human life and is inseparable from the spiritual and moral values. Love not only integrates, regulates and realizes separate moral values, but also the most through them is revealed, manifests, operates matures.
Keywords: love; spirituality; moral values; E. Fromm; K. Wojtyla; A.Paškus